PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA PADA MATAKULIAH BIOLOGI SEL - Nuril Hidayati (Bioilmi: Jurnal Pendidikan, 2017)
Achievement of learning objectives and learning competencies can be possessed by students through a process of learning experiences that are meaningful for students. Low learning results one of them caused by misunderstanding of the concept of matter. Understanding the concept of students can be improved in learning by using the model of learning think, talk, write. This study is a classroom action research consisting of two cycles, each cycle consisting of planning, implementation, observation, and reflection. Data analysis technique is done by calculating from the value obtained from the completeness of individual and classical. The result of the analysis shows that there is an increase of learning result 23,32% from cycle 1 to cycle 2.